Effect of dynamic strain ageing on environmental degradation of fracture resistance of low-alloy RPV steels in high-temperature water environments. (15th May 2019) - Que, Z.; Seifert, H.P.; Spätig, P.; Zhang, A.; Holzer, J.; Rao, G.S.; Ritter, S.
Highlights: Elastic plastic fracture mechanics tests on RPV steels with high DSA susceptibility revealed a clear, but moderate reduction of the fracture initiation resistance in high-temperature water. The reduction of fracture initiation increased with decreasing loading rate in the DSA temperature-strain rate range and was most pronounced in hydrogenated high-temperature water and at 288 °C. The stronger reduction of fracture resistance in hydrogenated high-temperature water was mainly due to the localization of plastic deformation by interaction between DSA and hydrogen. Abstract: Elastic plastic fracture mechanics tests on different low-alloy reactor pressure vessel (RPV) steels in air and various simulated light water reactor environments revealed a clear, but moderate reduction of the fracture initiation resistance of RPV steels with high susceptibility to dynamic strain ageing (DSA) in high-temperature water (HTW). In HTW, the reduction of fracture initiation resistance increased with decreasing loading rate and was most pronounced in hydrogenated HTW. The stronger reduction of fracture resistance in hydrogenated HTW was mainly due to the localization of plastic deformation by interaction between DSA and hydrogen.